Спи, моя радость, усни...: [стихи] / ред. Т. Рашина - Рашина Т. (Лучшие стихи и сказки малышам, 2009)
Экземпляры: ф.13 (2009) / Инвентарный номер: 45959 / Цена: / Авт.знак: С 72 / ГРНТИ: 17.82.10 / ББК: Д